The devil's breath ebook - Harris, Tessa (Dr. Thomas Silkstone Mystery, 2013)
A terrifying fog and a brutal murder are quite the case for an American anatomist in this historical mystery for fans of Caleb Carr. In 1783, a man staggers out of his cottage into the streets of Oxfordshire, shattering an otherwise peaceful evening with the terrible sight of his body shaking and heaving, eyes wild with horror. Many of the villagers believe the Devil himself has entered Joseph Makepeace, the latest victim of a "great fog" that darkens the skies over England like a Biblical plague. When Joseph's son and daughter are found murdered—heads bashed in by a shovel—the town's worst suspicions are confirmed: Evil is abroad and needs to be banished. A brilliant man of science, Dr. Thomas Silkstone is not one to heed superstition. But when he arrives at the estate of the lovely widow Lady Lydia Farrell, he finds that it's not just her grain and livestock at risk. A shroud of mystery surrounds Lydia's lost child, who may still be alive in a workhouse. A natural disaster fills the skies with smoke and ash, clogging the lungs of all who breathe it in. And the grisly details of a father's crime compel Dr. Silkstone to look for answers beyond his medical books—between the Devil and the deep blue sea... Praise for The Devil's Breath "Excellent.... Both literally and figuratively atmospheric, this will appeal to fans of Imogen Robertson's series set during the same period."— Publishers Weekly , starred review "A fascinating series...Harris is at her vivid best describing in precise, fearsome detail the "Great Fogg.""— The New York Times Book Review